Discriminated Functional Communication for Attention: Evaluating Fixed and Varied Durations of Reinforcer Availability. (3rd February 2016) - Balka, Kaitlin E.; Hausman, Nicole L.; Schaller, Erin; Kahng, SungWoo
Abstract : Discriminated functional communication (DFC) training has been used to teach children to attend to naturally occurring discriminative stimuli when manding for attention. In this study, the participant was taught to only mand for attention during experimenter non‐busy periods. The participant could only discriminate busy and non‐busy activities during more naturalistic varied reinforcer availability periods following prior exposure to a fixed duration of availability. These data suggest that DFC may first have to be taught under more predictable conditions prior to transitioning to more naturalistic conditions. Copyright © 2016 John Wiley & Sons, Ltd.